Chromosomal and cellular therapeutic approaches for Down syndrome: a research update - Huang, Tan; Fakurazi, Sharida; Cheah, Pike-See; Ling, King-Hwa (Elsevier, 2024)
In individuals with Down syndrome (DS), an additional HSA21 chromosome copy leads to the overexpression of a myriad of HSA21 genes, disrupting the transcription of the entire genome. This dysregulation in transcription and post-transcriptional modifications contributes to abnormal phenotypes across nearly all tissues and organs in DS individuals. The array of severe clinical symptoms associated with trisomy 21 poses a considerable challenge in the quest for a cure for DS. Fortunately, a wealth of research suggests that chromosome therapy, hinging on cutting-edge genome editing technologies, can potentially eliminate the extra copy of the human chromosome 21. Genome editing tools have demonstrated their efficacy in restoring trisomy to a normal diploid state in vitro DS cell models. Furthermore, we delve into the noteworthy findings in cellular therapy for DS, with recent studies showcasing the increasing feasibility of strategies involving stem cells and CAR T-cells to address corresponding clinical phenotypes.